2000
DOI: 10.1007/s002510050640
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the human interleukin-1 receptor antagonist gene IL1HY1

Abstract: The interleukin (IL)-1 family of proteins plays an important role in inflammatory and defense mechanisms. The recently characterized IL1HY1 cDNA encodes a new member of the IL-1 receptor antagonist family (IL-1ra). In this report, we describe the complete nucleotide sequence of the human IL1HY1 gene. We sequenced approximately 7,600 nucleotides and found four coding exons ranging in size from 55 to 2,288 nucleotides. The 5' untranslated region is formed by one of two alternatively used exons and one invariably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Since this subject was last reviewed almost a decade ago (Huising et al 2004), our work in the chicken has identified two IL-1 receptor antagonist genes for the first time in a non-mammalian species (Gibson et al 2012a; Gibson et al 2012b). The fact that they reside at an alternative locus to IL-1β yet retain structural and functional similarities with their mammalian orthologues suggests that the previous conjecture on the evolution of these two receptor antagonists is likely to be incorrect (Mulero et al 2000). An IL-1β antagonist in rainbow trout (Wang et al 2009) and three IL-1 genes in lizards that group with the chicken, human and mouse receptor antagonists (Gibson et al 2012a) have also been identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this subject was last reviewed almost a decade ago (Huising et al 2004), our work in the chicken has identified two IL-1 receptor antagonist genes for the first time in a non-mammalian species (Gibson et al 2012a; Gibson et al 2012b). The fact that they reside at an alternative locus to IL-1β yet retain structural and functional similarities with their mammalian orthologues suggests that the previous conjecture on the evolution of these two receptor antagonists is likely to be incorrect (Mulero et al 2000). An IL-1β antagonist in rainbow trout (Wang et al 2009) and three IL-1 genes in lizards that group with the chicken, human and mouse receptor antagonists (Gibson et al 2012a) have also been identified.…”
Section: Discussionmentioning
confidence: 99%
“…IL-36RN also interacts with the orphan receptor SIGIRR to downregulate inflammation through an as yet unelucidated mechanism (Costelloe et al 2008). The gene for IL-36RN is present in the genome sequence of over 30 mammalian species and was previously proposed to have arisen following gene duplication from IL-1RN in the ancestral species of the mammalian lineage (Mulero et al 2000). The chicken is the only non-mammalian species in which it has been identified to date (Gibson et al 2012b).…”
Section: The Chicken Il-1 Familymentioning
confidence: 99%
“…The proposed nomenclature for the IL-1 family are IL-1F1 (IL-1␣), IL-1F2 (IL-1␤), IL-1F3 (IL-1Ra), IL-1F4 (IL-18), IL-1F5 (IL-1H3, IL-1Hy1, FIL1␦, IL-1RP3, IL-1L1, and IL-1␦), IL-1F6 (FIL1⑀), IL-1F7 (human IL-1 homologue (IL-1H4), FIL1, IL-1RP1, and IL-1H), IL-1F8 (IL-1H2 and FIL), IL-1F9 (IL-1H1, IL-1RP2, and IL-1⑀), and IL-1F10 (IL-1Hy2 and FKSG75) (17)(18)(19)(20)(21)(22)(23)(24). Preliminary studies showed that these novel members also do not contain a hydrophobic leader sequence.…”
mentioning
confidence: 99%
“…The new members of the IL-1 family are derived from a common ancestor, as are IL-1 and IL-18 (11,12). Except for IL-18, each maps to the same region on human chromosome 2 (4,(11)(12)(13). On the basis of their structure these IL-1 family members potentially can act as agonistic or antagonistic ligands for members of the IL-1 receptor family; however, their biological function is presently unknown.…”
mentioning
confidence: 99%